Rom, Italien: Untersuchungen zur Bau- und Nutzungsgeschichte der Basilica Iulia im urbanistischen Kontext des Forum Romanum - Freyberger, Klaus Stefan (e-Forschungsberichte des DAI, 2023)
The first known basilica in the area was the Basilica Sempronia erected in 170 BC by the censor Titus Sempronius Gracchus behind the tabernae veteres. During the reign of Caesar, the building was named Basilica Iulia and got its final architectural setting. Two aisles which were formed by rows of pillars surrounded the central court on all sides. Near the northwestern corner of the building next to the lacus Servilius the so called arch of Tiberius was erected in Augustean times and probably dedicated by Tiberius. In its interior, the basilica presented itself as a luxurious utility building which was most of all equipped for mercantile and monetary purposes. As at so many Roman basilicas, probably also at the Basilica Iulia civil actions like financial tribunals took place.